Urine cytological study in patients with clinicopathologically confirmed neuronal intranuclear inclusion disease - Zhou, Yiyi; Huang, Pengcheng; Huang, Zhaojun; Peng, Yun; Zheng, Yilei; Yu, Yaqing; Zhu, Min; Deng, Jianwen; Wang, Zhaoxia; Hong, Daojun (Frontiers in Aging Neuroscience, 2022)
Objective The diagnosis of neuronal intranuclear inclusion disease (NIID) is currently based on CGG repeat expansion in the 5′UTR of the NOTCH2NLC gene, or p62-positive intranuclear inclusions in skin biopsy. The purpose of this study is to explore the value of non-invasive pathological findings in urine sediment cells from NIID patients. Materials and methods Ten patients with clinically suspected NIID were enrolled for skin biopsy and gene screening. Morning urine (500 ml) was collected from each patient, and cell sediment was obtained by centrifugation. Urine cytology, including Giemsa staining, p62 immunostaining, and electron microscopic examination, were conducted on cell sediment. Results The main clinical symptoms of 10 patients included episodic disturbance of consciousness, cognitive impairment, tremor, limb weakness, and so on. Cerebral MRI showed that 9 patients had linear DWI high signal in the corticomedullary junction. Genetic testing found that the number of CGG repeat ranged from 96 to 158 in the NOTCH2NLC gene. Skin biopsy revealed that all patients showed p62-positive intranuclear inclusions in 18.5 ± 6.3% of the duct epithelial cells of sweat gland. In contrast, urine sediment smears revealed that only 3 patients had p62 positive intranuclear inclusions in 3.5 ± 1.2% of the sedimentary cells. Ultrastructural examinations showed that intranuclear inclusions were also identified in the cell sediment of the 3 patients. Conclusion Urine cytology may be a new and non-invasive pathological diagnosis technique for some NIID patients, although the positive rate is not as high as that of skin biopsy, which is a sensitive and reliable pathological method for NIID.